Deranged language and silences: the relationships between madness, language and literature in Nadie me verá llorar by Cristina Rivera Garza - Martínez Díaz, María (2023)
This article reads the novel “Nadie me verá llorar” from the perspective of the relations between the language of madness and the language of sanity, and at the same time, the relations between the text, the subject, and the reader. In order to do this, I start by addressing the issue of madness as an absence or, an abundance of language, then, I look at the presence of pathos as a possibility of the existence of madness, and finally, I analyze the relationship between the reader and the text based on what I previously problematized. The notion of madness that I subscribe to for this analysis is the one proposed by Foucault (1972) in History of Madness, pointing out that it must be understood as a historical, cultural, and social construction since it is in constant transformation. Therefore, madness has a fickle character, which makes it impossible to fix.